Uncovering Trypanosoma spp. diversity of wild mammals by the use of DNA from blood clots. (April 2019) - Rodrigues, Marina Silva; Lima, Luciana; Xavier, Samanta Cristina das Chagas; Herrera, Heitor Miraglia; Rocha, Fabiana Lopes; Roque, André Luiz Rodrigues; Teixeira, Marta Maria Geraldes; Jansen, Ana Maria
Abstract: Trypanosoma spp. infection in wild mammals is detected mainly through parasitological tests that usually display low sensitivity. We propose the use of DNA extracted directly from blood clots (BC), which are neglected sources of DNA for diagnosis and identification of Trypanosoma spp. This approach followed by nested PCR targeting the 18S SSU rDNA demonstrated to be sensitive and suitable to evaluate the diversity of trypanosomes infecting sylvatic mammals, including subpatent and mixed infections. Infection was detected in 95/120 (79.2%) samples from bats, carnivores and marsupials that included negative serological and hemoculture testing mammals. Thirteen Trypanosoma spp. or Molecular Operational Taxonomic Units (MOTUs) were identified, including two new MOTUs. The high diversity of trypanosomes species and MOTUs infecting bats and marsupials showed that these hosts can be considered as bio-accumulators of Trypanosoma spp., with specimens of Didelphis spp. displaying the highest trypanosome diversity. The use of blood clots allowed direct access to non-culturable parasites, mixed infections, besides bypassing the selective pressure on the parasites inherent to cultivation procedures. Trypanosoma cruzi was the species found infecting the highest number of individuals, followed by T. lainsoni. Positive PCR for T. cruzi was observed in 16 seronegative individuals and 30 individuals with negative hemocultures. Also, T. lainsoni, previously found only in rodents, showed to be capable of infecting bats and marsupials. This finding makes it clear that some species of Trypanosoma are more generalist than previously thought. Molecular diagnosis using nested PCR from DNA extracted from BC allowed the increase of the knowledge about host-spectrum and distribution of Trypanosoma spp. and allowed the identification of new MOTUs. Graphical abstract: Image 1 Highlights: Blood clots are suitable as DNA source for Trypanosoma spp. identification. Detection of T. cruzi infection in seronegative wild mammals by PCR of blood clots. Trypanosoma spp. identified in individuals with negative hemoculture. T. dionisii, T. cascavelli and T. lainsoni have a broader host spectrum. Two new MOTUs were identified in Didelphis sp. and Carollia sp.